Baseline characteristics and treatment cost of hepatitis C at Hospital for Tropical Diseases, Ho Chi Minh City, Vietnam in Direct-Acting Antiviral treatment era - Dung, NT; Thanh, TTT; Ngọc, NM; Nguyen, HA; Phuong, LT; Quang, VM; Rahman, M; Hung, LM (ACT Publishing Group Ltd, 2019)
Background: Direct-Acting Antivirals (DAAs) are recommended as first-line of drugs for the treatment of chronic hepatitis C virus (HCV) infection in Vietnam in 2016. Since then, Hospital for Tropical Diseases (HTD), Ho Chi Minh City, Vietnam introduced DAAs based treatment for all newly presented chronic HCV patients. Here, we report the sociodemographic, clinical, biochemical, and virologic characteristics of patients and the direct medical cost associated with DAAs treatment. Methods: We conducted a retrospective cross-sectional study among chronic HCV patients attended at HTD from March 2016 to October 2017 and treated with DAAs. We used an extract of the patient’s electronic medical record containing demographics, clinical presentations, laboratory results, drug prescription, and cost of treatment at the hospital for data analysis. Results: 2817 chronic HCV patient received DAAs treatment during the study period. The mean age was 55.0 years, and 54.9% (1546/2817) of the patients were female. HCV genotype 1, 2, 3 and 6 prevalence was 32.1% (904/2817), 12.7% (359/2817), 0.4% (10/2817), and 54.7% (1542/2817) respectively. The mean HCV viral load was 3.1 × 106 copies/ml, including 46.9% (1322/2817) had ≥106 copies/ml. 70.64% (1990/2817) and 16.15% (455/28817) of the patients received Sofosbuvir (SOF)/Ledipasvir (LDV) ± Ribavirin (RBV) and SOF/Daclatasvir (DCV) ± RBV therapy respectively. The average drug cost for a 12-week of SOF/LDV ± RBV and SOF/DCV ± RBV treatment was US$2068 - 2230 and US$2417 - 2472, respectively. Conclusion: Genotype 6 was the most predominant genotype in southern Vietnam. The preferred treatment for chronic HCV infection was SOF/LDV ± RBV for 12 weeks.